THE EVALUATION OF INTERFACE DESIGN PRINCIPLES ON TERRAS WEBSITE (PUBLIC FACILITY LOAN PLATFORM OF TELKOM UNIVERSITY) - Anjar Sari, Siwi; Bintang Nugraha (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2025)
The TERRAS website is a platform for students and staff at Telkom University to check room availability. However, users encounter several issues, such as an unintuitive interface, confusing navigation, and inconsistent design. Therefore, this study evaluates the interface design of the TERRAS website based on three key principles: simplicity, consistency, and perceptibility, as developed by Don Norman, Jakob Nielsen, Larry Constantine, and Lucy Lockwood. This research employs a qualitative method, conducting in-depth interviews with students as primary users and logistics staff as website facilitators. Additionally, observations were made on other Telkom University websites to compare their level of consistency. The findings indicate that the TERRAS website lacks consistency compared to other Telkom University websites. While the simplicity aspect is fairly adequate, the website lacks informativeness. Moreover, perceptibility needs improvement to enhance the user experience. Improvements in interface design are necessary to increase usability and website effectiveness. The recommendations from this study are expected to serve as a foundation for developers to optimize the TERRAS website design, making it more user-friendly and aligned with users' needs.